Coordinating for Good Governance - Wolfowitz, Paul (2016)
Paul Wolfowitz, President of the World Bank, discussed good governance, policies, and practice that are the means to achieve better development results. He spoke of sound principles of accountability and transparency that not only assure funds that are spent as intended, but also are essential to accelerating economic growth, helping the poor to escape poverty,and achieving the Millennium Development Goals. He highlighted the need to find solutions which are innovative and flexible and which respect the unique constituents and conditions in each country. He concluded by saying that the effort to strengthen and improve governance is a key element in the fight against poverty.